Structural Evaluation of Reinforced Concrete Beams Retrofitted using Cold-Formed Steel Plates - Ambar Susanto; Urwatul Wusqo; Amirah Zakiyyah; Ira Puspitasari; Heri Kasyanto; Mardiana Oesman; Susilahadi (Department of Civil and Environmental Engineering, Faculty of Engineering, Universitas Gadjah Mada, 2026)
Shear strengthening of reinforced concrete (RC) beams has become increasingly important for improving the safety and durability of existing structures. This study focuses on the behavior of RC beams strengthened using cold-formed steel plates installed diagonally at a 45-degree angle. Two beam specimens with dimensions of 250 × 400 × 1500 mm were tested under continuous loading: a control beam (B0) without strengthening and a strengthened beam (B1) with a single cold-formed steel plate bonded to the beam web. Additionally, a Linear Variable Differential Transformer (LVDT) was installed at midspan, ¼ span, and ¾ span to monitor deflections, with all instrumentation connected to a data acquisition system. Test results showed that the initial yielding load for the control specimen B0 was 283.07 kN, while the strengthened specimen B1 yielded at 288.91 kN, indicating a 2.44% increase in initial yield load due to the presence of the cold-formed steel plate. Loading was continued up to 350 kN, at which point the midspan deflection of B0 was measured at 21.40 mm, whereas B1 exhibited a lower deflection of 17.81 mm, demonstrating improved stiffness and reduced deformation. The shear capacity of the beams, which includes contributions from both the concrete and shear reinforcement, was calculated as 145.59 kN. This shear capacity corresponded to a total applied load of 291.18 kN, marking the limit at which shear failure is expected to occur. The cracks on the both left and right side of the beams seem symmetrically and there is no separation between the concrete and the cold-formed steel plates. The study confirms that retrofitting RC beams with diagonally installed cold-formed steel plates can effectively enhance their shear capacity and stiffness. This strengthening technique offers a practical and efficient method for extending the service life of existing concrete structures.